Large controlling shareholders and stock price synchronicity - Boubaker, Sabri; Mansali, Hatem; Rjiba, Hatem (Journal of Banking & Finance, 2014)
This paper examines the effect of controlling shareholders on stock price synchronicity by focusing on two salient corporate governance features in a concentrated ownership setting, namely, ultimate cash flow rights and the separation of voting and cash flow rights (i.e., excess control). Using a unique dataset of 654 French listed firms spanning 1998–2007, this study provides evidence that stock price synchronicity increases with excess control, supporting the argument that controlling shareholders tend to disclose less firm-specific information to conceal opportunistic practices. Additionally, this study shows that firms with substantial excess control are more likely to experience stock price crashes, consistent with the conjecture that controlling shareholders are more likely to hoard bad information when their control rights exceed their cash flow rights. Another important finding is that firms’ stock prices are less synchronous and less likely to crash when controlling shareholders own a large fraction of cash flow rights. This is consistent with the argument that controlling shareholders have less incentive to adopt poor disclosure policies and to accumulate bad news, since high cash flow ownership aligns their interests with those of minority investors.